The aetiology and impact of malnutrition in paediatric inflammatory bowel disease - Gerasimidis, K.; Mcgrogan, P.; Edwards, Christine (2011)
Disease-associated undernutrition of all types is very common in paediatric inflammatory bowel disease (IBD). Recent weight loss remains one of the triad of clinical manifestations and a cornerstone for the diagnosis of Crohn's disease (CD), although significantly fewer patients now present as being underweight. Recent evidence suggests that the introduction of medical treatment will quickly restore body weight, although this does not reflect concomitant changes in body composition. CD children present with features of nutritional cachexia with normal fat stores but depleted lean mass. Poor bone health, delayed puberty and growth failure are additional features that further complicate clinical management. Suboptimal nutritional intake is a main determinant of undernutrition, although activation of the immune system and secretion of pro-inflammatory cytokines exert additional independent effects. Biochemically low concentrations of plasma micronutrients are commonly reported in IBD patients, although their interpretation is difficult in the presence of an acute phase response and other indices of body stores adequacy are needed. Anaemia is a common extraintestinal manifestation of the IBD child. Iron-deficient anaemia is the predominant type, with anaemia of chronic disease second. Decreased dietary intake, as a result of decreased appetite and food aversion, is the major cause of undernutrition in paediatric IBD. Altered energy and nutrient requirements, malabsorption and increased gastrointestinal losses are additional factors, although their contribution to undernutrition in paediatric CD needs to be studied further. © 2011 The Authors. Journal of Human Nutrition and Dietetics © 2011 The British Dietetic Association Ltd.